Development of an alternative for corrosive resistant galvanized steel compatible for laser welding. (2021) - Sinha, Amit Kumar; Anand, Ankush
Abstract: Corrosion is the most challenging issue for any manufacturing industry, particularly for automotive and shipbuilding. Although, galvanized steel has some attractive features like long life, toughest coating, and automatic protection for damaged areas. It is quite difficult to weld the galvanized steel because the formation of spatter cannot be ignored during the joining of galvanized steel. The major reason for the formation of spatter is due to the large difference of melting point between Fe (1538 °C) and, Zn (906 °C). Therefore, to develop an alternative of galvanized steel which will be more susceptible to joining of galvanized steel is a more challenging task. To full fill the requirement of manufacturing industries, in this research we have suggested how to develop such alloy which will be a strong corrosive resistant keeping intake the properties of galvanized steel as well as easy to do laser welding.